Foliar turnover rates in Finland - comparing estimates from needle-cohort and litterfall-biomass methods - Tupek, Boris; Mäkipää, Raisa; Heikkinen, Juha; Peltoniemi, Mikko; Ukonmaanaho, Liisa; Hokkanen, Tatu; Nojd, Pekka; Nevalainen, Seppo; Lindgren, Martti; Lehtonen, Aleksi (Finnish Environment Institute, 2016)
Soil carbon models serving national greenhouse gas (GHG) inventories need precise litter input estimates that typically originate from regionally-averaged and species-specific biomass turnover rates. We compared the foliar turnover rates estimated from long-term measurements by two methods: the needle-cohort based turnover rates (NT; 1064 Scots pine and Norway spruce stands), used in Finnish GHG inventory, and litterfall-biomass based turnover rates (LT; 40 Scots pine, Norway spruce, and silver and downy birch stands). For evergreens, regionally averaged NT values (+/- SD) (0.139 +/- 0.01, 0.1 +/- 0.009 for spruce south and north of 64 degrees N, and 0.278 +/- 0.016, 0.213 +/- 0.028 for pine, respectively) were greater than those used in the GHG inventory model in Finland (0.1, 0.05 for spruce in the south and north, and 0.245, 0.154 for pine, respectively). For deciduous forests, averaged LT values SD (0.784 +/- 0.162, 0.634 +/- 0.093 for birch in the south and north) were close to that (0.79) currently used for the whole of Finland. Peer reviewed